DESAIN PENCAHAYAAN RUANG RAWAT INAP KELAS ATAS RS. DARMO DAN ST. VINCENTIUS A. PAULO SURABAYA - Indrani, Hedy C.; Santosa, Ika Puspita (Dimensi Interior, 2009)
Inpatient rooms in Dutch colonial heritage hospitals have some unique physical characteristics related to lighting, such as the height of the building structure and the use of terazzo for wall and floor finishing. These characteristics cause the atmosphere of the hospital to appear bleak since the amount of lighting illumination in the rooms is not fulfilled. The purpose of this research is to analyze and find solutions for optimal lighting design by taking the case of the upper-class wards in two Dutch colonial hospitals in Surabaya: the RS Darmo and the SSR St. Vincentius A Paulo. The first step is observation and measurement using Lightmeter LX-103 to determine the amount of turning on the instrument room, followed by verification and simulation optimization using a computer program of DIALux v.4.6. The analysis showed that the lighting conditions on the wards at both hospitals have not met the optimum standards. Thus, there are several ways to optimize light levels, including: the replacement of materials and colors of the walls and floors with brighter colors, decreasing the ceiling height using a drop ceiling, replacement of the colors of the furniture with brighter colors, and the use of 28-36W fluorescent lamp and soft white 26W down lighting.